Bavardages et masculinités au xviie siècle - Nicholas Hammond (Itinéraires)
This article concerns the close connection between gossip and the expression of male same-sex desire in seventeenth-century France. Traditionally associated with the negative qualities imputed to women or serving as a covert vehicle for the playing out of social and political rivalries, gossip is here shown to have had an important and positive function: affording a space for groups which were not otherwise allowed a voice.